PESANTREN SALAFIYAH DI ERA GLOBALISASI - Hasbi Indra (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
The research qualitative  to the traditional  islamic  boarding school  (pesantren salafiyah)are basesthe scholar  prespektive through  books,  journals  and  so  on  with  descriptive analisys  by normative, filosofis and sociologis.The research are tries to description how pesantren salafiyah have 1.800.000 more students to readiness of them  to face the fenomenan globalization  era. Pesantren salafiyah areborn in colonialismat Walisongoera as a institution  learn  Islamic  knowledge. Those  all institutionare established by community and  now  thats  atthe remote area.  The  institutionsnow have  1.882.901 of 3.876.696 student and  18.232 of 29.535 institutions  from three  types of be traditional  pesantren, combinate pesantren and  modem pesantren. Thatinstitution just learn Islamic  knowledge through  Islamic  classical  texbook (kitab  kuning)  most  of institution  are  not learn  science such  as MIFA. The traditional  pesantren now  are  faced  of globalization  fenomenon.Globalization in this era are  the  human relation  with unlimited time  in the  world.  Through  the  development of toolscommunications or throughfaxcimile, human as faras  have  an  information in the  other  continents. We  wach  TV a wars  saw sad  the happens, like wars  soldier  American  and  Irak, islamic  state  Irak and  Syria (ISIS) breakthroughislamic inherited the golden era.The fenomenon of the develompement of technology in globalization era are challengs of pesantren Salafiyah. Its istitutions must product alumnus are ready competete with knowledge, scineces and even skill and santri are introduce with tools of technology learning. So, all santri’s must all ready compatete the globalization  era, and the institution must manage with professional